Pro-cyclical capital regulation and lending - Markus Behn; Rainer Haselmann; Paul Wachtel (Deutsche Bundesbank, 2014)
We use a quasi-experimental research design to examine the effect of model-based capital regulation introduced under the Basel II agreement on the pro-cyclicality of bank lending and firms' access to funds during a recession. In response to an exogenous shock to credit risk in the German economy, loans subject to modelbased, time-varying capital charges were reduced by 3.5 percent more than loans under the traditional approach to capital regulation. The effect is even stronger when we examine aggregate firm borrowing, suggesting that the pro-cyclical effect of model-based capital charges is not offset by substitution to other banks which use the traditional approach.
Keywords: G01; G21; G28; 330; capital regulation; credit crunch; financial crisis